KEANEKARAGAMAN JENIS TUMBUHAN OBAT TRADISIONAL DAN PEMANFAATANNYA PADA SUKU KULAWI DI DESA MATAUE KAWASAN TAMAN NASIONAL LORE LINDU - Suhendar Arham; Akhmad Khumaidi; Ramadhanil Pitopang (Biology Department, Mathematics and natural science, Tadulako University, 2016)
Ethnobotany is the study of medicinal plants of plant utilization in both everyday and cultural mores of a nation. The objective of this research was to identified the diversity of traditional medical plant and its utilization in kulawi local people at Mataue village Lore Lindu National Park. The research was conducted during April to May 2014 at Kulawi Sub-district of Sigi Regency Central Sulawesi. Identification process had been done at Biodiversity Laboratory, Faculty of Mathematics and Natural Sciences, Tadulako University. Methods which used on this study were survey and descriptive, consists of field survey and semi structural interview based on questionnaire. Outcome of the research showed that there were 49 plant species covered from 30 families which were traditionally used as medicine. Leaves organ was the most widely applied as medicine with 58% percentage, habitus type which highly found was herbaceous type with 51% percentage, and the most treated disease by the traditional medicine was non-communicable disease as much as 36%. Key words :Ethno botany, Medical Plant, Kulawi Local People.